Stunning of neutrophils accounts for the anti-inflammatory effects of clodronate liposomes - Culemann, Stephan; Knab, Katharina; Euler, Maximilien; Wegner, Anja; Garibagaoglu, Hilal; Ackermann, Jochen; Fischer, Kim; Kienhoefer, Deborah; Crainiciuc, Georgiana; Hahn, Jonas; Grüneboom, Anika; Nimmerjahn, Falk; et al. (Journal of Experimental Medicine, 2023)
The authors show that the anti-inflammatory effects of clodronate liposomes do not result from the depletion of mononuclear phagocytes but from a functional stunning of polymorphonuclear neutrophils. These findings necessitate a critical revision of the current literature on the role of monocytes and macrophages in inflammation.
CRIS-Team WoS Importer:2023-04-28